Wang Yangming, Descartes, and the Sino-European juncture of Enlightenment. Issue 3 (3rd July 2021) - Zheng, Zemian
ABSTRACT: Wang Yangming is the founder of Chinese Enlightenment in the Ming-Qing period, in a similar way Descartes is for the European. The European Enlightenment thinkers such as Leibniz and Voltaire had been inspired by China about the human being's ethical independence at the collective level, namely, the ability of a community to lead an ethical life independent of God's revelation. Meanwhile, the Enlightenment thinkers failed to notice the Chinese intellectual resources that encourage human being's ethical independence at the individual level, namely, the belief that every human individual is equally capable of leading one's ethical life purely relying on one's own good judgment. For this point, Wang Yangming is the resources that the West could have drawn upon. Both Wang Yangming and Descartes assert the egalitarianism about every individual's power of judgment. I label this similarity as the 'Sino-European juncture of Enlightenment.' Other similarities between these two thinkers lie, firstly, in their common strategy in defending egalitarianism: both give a psychological account of the sources of error by analyzing the relationship between will and reason; and secondly, in their methodology: both redefine the method of attaining knowledge, and both emphasize that one should start from the plain, simple and insignificant things and then ascend to the complex things at issue.